ZIF-67 (at) ATP (adenosine triphosphate) composite adsorption material, preparation method thereof and application of ZIF-67 (at) ATP composite adsorption material in formaldehyde adsorption

Through the composite and particle size regulation of ZIF-67 and ATP, an adsorption material with a sea urchin-like structure is formed, which solves the competitive adsorption and environmental pollution problems of existing adsorption materials in formaldehyde adsorption, and achieves a high-efficiency and low-cost formaldehyde adsorption effect.

CN119588325APending Publication Date: 2025-03-11JIANGSU NAO NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411937056.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing adsorption materials are prone to problems such as competitive adsorption, adsorption saturation and desorption when adsorbing formaldehyde, and are costly and have serious environmental pollution, making it difficult to apply on a large scale in the industrial field.

Method used

By combining ZIF-67 with ATP, the particle size of the material is regulated, and the concave and concave rock stones are interspersed into the polyhedral crystal structure of ZIF-67 to form a sea urchin-like structure, improving the stability and adsorption capacity of the material, and using ethanol as a solvent to reduce environmental pollution.

Benefits of technology

It improves the stability of composite materials and the adsorption capacity of formaldehyde, reduces costs and environmental pollution, simplifies the process flow, and broadens the application scope of natural mineral materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588325A_ABST
    Figure CN119588325A_ABST
Patent Text Reader

Abstract

The invention discloses a ZIF-67 (at) ATP composite adsorption material, a preparation method thereof and application of the ZIF-67 (at) ATP composite adsorption material in formaldehyde adsorption. The ZIF-67 (at) ATP composite adsorption material with a sea urchin-shaped structure is prepared by using ethanol as a solvent, cobalt nitrate hexahydrate and dimethylimidazole as raw materials and attapulgite as a carrier substrate. The prepared composite material has an excellent adsorption effect on formaldehyde, and the adsorption performance in a high-humidity water vapor environment is improved. According to the invention, the natural porous mineral is used as the substrate material, and the low-toxicity substance is used as the solvent, so that the use of expensive raw materials is reduced, the cost is low, the preparation process is simple, the residue of harmful byproducts is reduced, and the environmental pollution is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of adsorption materials, and specifically relates to a ZIF-67@ATP composite adsorption material and a preparation method thereof and application thereof in formaldehyde adsorption. Background Art

[0002] According to statistics, at least one-third of human activities are carried out outdoors, so the quality of air will directly affect people's health. Due to the pollution of industrial waste gas, there are many harmful substances in the air, such as bacteria, viruses, PM2.5, VOCs, etc. Among them, organic compounds represented by formaldehyde pose the greatest threat to people's health. Therefore, eliminating formaldehyde pollution is crucial to protecting people's health and improving their quality of life.

[0003] Traditional porous materials, such as inorganic materials such as the natural porous mineral attapulgite, are currently the mainstream formaldehyde adsorption materials because of their excellent specific surface area, stable chemical properties, abundant resources and low price. However, in practical applications, the adsorption environment is complex and changeable, which easily leads to competitive adsorption, adsorption saturation and desorption. For example, attapulgite has a large number of -OH groups on its surface, and its adsorption effect is poor in a water vapor environment, which limits its large-scale application in the industrial field.

[0004] ZIF-67 is a metal organic framework (MOFs) material that has attracted extensive attention from researchers due to its unique structural characteristics. MOFs are self-assembled by coordination bonds between different metal ions and organic ligands or clusters. Compared with traditional adsorption materials, MOFs have a larger specific surface area and better pore structure, so they are widely used in gas adsorption, catalysis and other fields. However, single MOFs materials are not stable enough, and the skeleton is easy to collapse, which may cause problems such as agglomeration, difficulty in recycling, and secondary pollution, making it difficult to directly use them in various application scenarios. At the same time, its high raw materials also limit its large-scale application. Therefore, MOFs are usually used in combination with other substrate materials. For example, Yang Junjie et al. (High-strength and high-toughness nanofibers loaded with ZIF-67 and formaldehyde adsorption performance. Journal of Basic Sciences of Textile Colleges and Universities, 2022, 35(4): 8-15.) immersed the nanofibers in a fixed ratio of cobalt nitrate and 2-methylimidazole solution to make ZIF-67 particles grow on the surface of the nanofibers to prepare ZIF-67@PES / TPU composite membranes. However, the adsorption effect of nanofibers themselves is poor. The non-powdered nature of nanofibers limits their application in fields such as industrial exhaust gas treatment. The choice of methanol as a solvent during preparation also increases environmental pollution.

[0005] The present invention selects a suitable MOFs material (ZIF-67) and a suitable clay mineral substrate (ATP), and selects ethanol as a solvent, which is conducive to giving full play to the carrier function and adsorption capacity of the porous mineral, improving the stability and hydrophobicity of the material, simplifying the process flow, reducing production costs, and also reducing environmental pollution. Summary of the invention

[0006] The purpose of the present invention is to provide a ZIF-67@ATP composite adsorption material and a preparation method thereof and application thereof in formaldehyde adsorption. The present invention regulates the particle size of ZIF-67 so that attapulgite is inserted into the polyhedral crystal structure of ZIF-67, presenting a sea urchin-like feature, thereby improving the stability of the composite material and the adsorption capacity of formaldehyde.

[0007] The technical solution adopted by the present invention is: The present invention first provides a composite material (ZIF-67@ATP) of a metal organic framework (ZIF-67) and a clay mineral attapulgite (ATP). The attapulgite is orderly interspersed in the polyhedral crystal structure of ZIF-67, presenting a sea urchin shape, and its particle size is 200-500nm.

[0008] Furthermore, in the ZIF-67@ATP composite material, the mass ratio of ZIF-67 to ATP is 0.02~0.08:1.

[0009] The present invention further provides a method for preparing the above-mentioned ZIF-67@ATP composite adsorption material, comprising the following specific steps: (1) Weigh a certain amount of cobalt nitrate hexahydrate (Co(NO3)2·6H2O), slowly add it to anhydrous ethanol solvent under ultrasonic environment, and stir with a glass rod until it is completely dissolved. This is recorded as solution A.

[0010] Among them, the mass concentration of Co(NO3)2·6H2O is 15~35 mg / mL.

[0011] (2) Weigh a certain amount of dimethylimidazole, slowly add it to anhydrous ethanol solvent under ultrasonic environment, and stir with a glass rod until it is completely dissolved. This is recorded as solution B.

[0012] Among them, the amount of dimethylimidazole is calculated according to the amount of Co(NO3)2·6H2O, the mass ratio of dimethylimidazole to Co(NO3)2·6H2O is 1~10:1, and the mass concentration of dimethylimidazole is 16~170 mg / mL.

[0013] (3) Solution B is slowly added to solution A under mechanical stirring. When the solution completely turns purple, the mixture is reacted at room temperature for a certain period of time to obtain a ZIF-67 precursor solution.

[0014] The reaction time at room temperature is 1 to 6 h.

[0015] (4) Weigh a certain amount of attapulgite, disperse it into the ZIF-67 precursor solution by ultrasonic vibration and mechanical stirring, react at room temperature for a certain period of time, let it stand and precipitate, collect the solid product by centrifugation, wash with alcohol, and dry to obtain a metal organic framework and attapulgite composite adsorption material (ZIF-67@ATP).

[0016] Among them, the amount of attapulgite is calculated according to the amount of Co(NO3)2·6H2O, the mass ratio of Co(NO3)2·6H2O to attapulgite is 0.15~0.7:1, the amount of attapulgite is 0.5~2 g, the mass ratio of ZIF-67 to attapulgite is 0.02~0.08:1, the stirring reaction time is 12~24 h, the drying temperature is 80~100℃, and the drying time is 8~12 h.

[0017] The present invention further provides the use of the ZIF-67@ATP material in the adsorption of volatile organic compounds, and the composite material still has good adsorption performance in a high humidity environment.

[0018] In a specific embodiment of the invention, formaldehyde was used as a simulated gas to perform static and dynamic adsorption to evaluate the adsorption performance of ZIF-67@ATP. The results show that the composite adsorption material of the present invention has a good adsorption effect on formaldehyde.

[0019] The beneficial effects of the present invention are: 1. The present invention composites a metal organic framework with a clay mineral attapulgite, inserts attapulgite into the metal organic framework, and improves the stability of the material and its ability to fix adsorbed gas by regulating the particle size of the material.

[0020] 2. The present invention compounds the metal organic framework with the clay mineral attapulgite, which reduces the competitive adsorption of natural clay minerals to water vapor and improves the hydrophobicity of the material to a certain extent.

[0021] 4. The present invention has fewer steps for preparing the composite adsorption material, is simple to operate, and has mild and easy-to-control conditions.

[0022] 5. Attapulgite, one of the raw materials of the present invention, is a natural mineral material, which reduces the cost, further broadens the application scope of natural mineral materials, and improves the resource utilization rate of natural mineral materials.

[0023] 6. The present invention does not select commonly used methanol as the solvent, but selects low-toxic ethanol as the solvent, which reduces the residual harmful by-products to a certain extent and reduces environmental pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 X-ray diffraction patterns (XRD) of the adsorbents of the samples prepared in Example 3 and Comparative Examples 3 and 5.

[0025] Figure 2 The infrared spectra (FT-IR) of the adsorbents of the samples prepared in Example 3 and Comparative Examples 3 and 5 are shown.

[0026] Figure 3 This is the scanning electron microscope (SEM) image of Example 3.

[0027] Figure 4 This is the scanning electron microscope (SEM) image of Comparative Example 2.

[0028] Figure 5 This is the scanning electron microscope (SEM) image of Comparative Example 3.

[0029] Figure 6 This is the scanning electron microscope (SEM) image of Comparative Example 5.

[0030] Figure 7 It is a dynamic penetration curve diagram of Examples 1 and 3 and Comparative Example 2 at 0% humidity.

[0031] Figure 8 It is a dynamic penetration curve diagram of Examples 1 and 3 and Comparative Example 2 at 80% humidity. DETAILED DESCRIPTION

[0032] The present invention is described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.

[0033] The attapulgite used in the following specific examples of the present invention was selected from Jiangsu Naou New Materials Co., Ltd. and was pre-dried before the experiment; the chemicals used were selected from Shanghai Aladdin Chemical Co., Ltd. Example 1

[0034] 1. Weigh 0.328 g of Co(NO3)2·6H2O, slowly add it into 20 mL of anhydrous ethanol solvent under ultrasonic environment, and stir with a glass rod until it is completely dissolved. This is recorded as solution A.

[0035] 2. Weigh 0.328 g of dimethylimidazole and slowly add it to 20 mL of anhydrous ethanol solvent under ultrasonic environment. Use a glass rod to stir until it is completely dissolved. This is recorded as solution B.

[0036] 3. Slowly add solution B into solution A under mechanical stirring. When the solution turns completely purple, react at room temperature for 1 h to obtain a ZIF-67 precursor solution.

[0037] 4. Weigh 1 g of attapulgite and disperse it into the ZIF-67 precursor solution by ultrasonic vibration and mechanical stirring. Stir the reaction at room temperature for 12 h, let it stand overnight, collect the solid product by centrifugation, wash it with alcohol, and dry it at 80 °C for 12 h to obtain a metal organic framework and attapulgite composite adsorption material (ZIF-67@ATP-1). Example 2

[0038] 1. Weigh 0.328 g of Co(NO3)2·6H2O, slowly add it into 20 mL of anhydrous ethanol solvent under ultrasonic environment, and stir with a glass rod until it is completely dissolved. This is recorded as solution A.

[0039] 2. Weigh 1.64 g of dimethylimidazole and slowly add it to 20 mL of anhydrous ethanol solvent under ultrasonic environment. Use a glass rod to stir until it is completely dissolved. This is recorded as solution B.

[0040] 3. Slowly add solution B into solution A under mechanical stirring. When the solution turns completely purple, react at room temperature for 3 h to obtain a ZIF-67 precursor solution.

[0041] 4. Weigh 1 g of attapulgite and disperse it into the ZIF-67 precursor solution by ultrasonic vibration and mechanical stirring. Stir the reaction at room temperature for 18 h, let it stand overnight, collect the solid product by centrifugation, wash it with alcohol, and dry it at 100 °C for 10 h to obtain a metal organic framework and attapulgite composite adsorption material (ZIF-67@ATP-2). Example 3

[0042] 1. Weigh 0.328 g of Co(NO3)2·6H2O, slowly add it into 10 mL of anhydrous ethanol solvent under ultrasonic environment, and stir with a glass rod until it is completely dissolved. This is recorded as solution A.

[0043] 2. Weigh 3.28 g of dimethylimidazole and slowly add it to 20 mL of anhydrous ethanol solvent under ultrasonic environment. Use a glass rod to stir until it is completely dissolved. This is recorded as solution B.

[0044] 3. Slowly add solution B into solution A under mechanical stirring until the solution completely turns purple. React at room temperature for 6 h to obtain a ZIF-67 precursor solution.

[0045] 4. Weigh 1 g of attapulgite and disperse it into the ZIF-67 precursor solution by ultrasonic vibration and mechanical stirring. Stir the reaction at room temperature for 24 h, let it stand overnight, collect the solid product by centrifugation, wash it with alcohol, and dry it at 120 °C for 8 h to obtain a metal organic framework and attapulgite composite adsorption material (ZIF-67@ATP-3). Comparative Example 1

[0046] 1. Prepare the ZIF-67 precursor solution according to Example 3.

[0047] 2. Weigh 0.5 g of attapulgite and disperse it into the ZIF-67 precursor solution by ultrasonic vibration and mechanical stirring. Stir the reaction at room temperature for 12 h, let it stand overnight, collect the solid product by centrifugation, wash it with alcohol, and dry it at 80 °C for 12 h to obtain a metal organic framework and attapulgite composite adsorption material (ZIF-67@ATP-4). Comparative Example 2

[0048] 1. Prepare the ZIF-67 precursor solution according to Example 3.

[0049] 2. Weigh 2 g of attapulgite and disperse it into the ZIF-67 precursor solution by ultrasonic vibration and mechanical stirring. Stir and react at room temperature for 12 h, let it stand overnight, collect the solid product by centrifugation, wash with alcohol, and dry at 80 °C for 12 h to obtain a metal organic framework and attapulgite composite adsorption material (ZIF-67@ATP-5). Comparative Example 3

[0050] A ZIF-67 precursor solution was prepared by referring to Example 1, and the reaction was stirred at room temperature for 12 h, and the solution was allowed to stand overnight. The solid product was collected by centrifugation, washed with alcohol, and dried at 80° C. for 12 h to obtain a metal organic framework adsorption material (ZIF-67-1). Comparative Example 4

[0051] A ZIF-67 precursor solution was prepared by referring to Example 2, and the reaction was stirred at room temperature for 18 h, allowed to stand overnight, the product was collected by centrifugation, washed with alcohol, and dried at 100° C. for 10 h to obtain a metal organic framework adsorption material (ZIF-67-2). Comparative Example 5

[0052] A ZIF-67 precursor solution was prepared by referring to Example 3, and the reaction was stirred at room temperature for 24 h, and allowed to stand overnight. The solid product was collected by centrifugation, washed with alcohol, and dried at 120° C. for 8 h to obtain a metal organic framework adsorption material (ZIF-67-3). Comparative Example 6

[0053] The ZIF-67 material prepared according to the method of Comparative Example 5 was ball-milled with attapulgite powder at a mass ratio of ZIF-67 to attapulgite powder of 1:1, and the ball milling was performed at 600 r / min for 6 h to obtain a ZIF-67+ATP physically mixed adsorption material. Material characterization

[0054] Figure 1 The crystal structures of Example 3 and Comparative Examples 3 and 5 were analyzed by XRD. Figure 1It can be seen that comparative examples 3 and 5 have characteristic peaks corresponding to ZIF-67 crystals at 7.4°, 10.5°, 12.8°, 14.8°, 16.6°, 18.0°, 22.2°, 24.7°, and 26.7°, and Co(NO3)2·6H2O and dimethylimidazole do not affect the formation of ZIF-67. After ZIF-67 is compounded with attapulgite, the peak type of Example 3 is weakened, but the characteristic peak still exists, and a characteristic peak belonging to attapulgite appears at 8.8°. This phenomenon shows that after the material is compounded, its characteristic peak is weakened, but the crystal structure is not changed, indicating that the ZIF-67@ATP-3 composite material is successfully prepared.

[0055] Figure 2 FT-IR test was performed on Example 3 and Comparative Examples 3 and 5. It can be seen from the infrared spectrum that In Comparative Examples 3 and 5, 1646 cm −1 and 1429 cm −1 -COO- stretching vibration; 1110cm −1 The C—O bond of the alcohol hydroxyl group. 1583cm −1 is the stretching vibration of the C=N bond in dimethylimidazole, 670-760 cm− 1 The out-of-phase and in-phase bending vibrations of C—H are 990-1420 cm −1 The band at 1100 cm-1 belongs to the C—N stretching vibration of ZIF-67, indicating that the ZIF-67 material was successfully synthesized. −1 The stretching vibration peak of Si-O-Si belonging to attapulgite appears, indicating the successful preparation of ZIF-67@ATP-3 composite material.

[0056] Figure 3 , Figure 4 and Figure 5 , Figure 6 The SEM images of ZIF-67@ATP-3, ZIF-67@ATP-5, ZIF-67-1, and ZIF-67-3 are shown respectively. Figure 3 , Figure 4 It can be observed that the composite of ZIF-67@ATP-3 is better, and the attapulgite is orderly interspersed in the polyhedral crystal structure of ZIF-67, showing a sea urchin shape, while ZIF-67@ATP-5 has more attapulgite added, which makes it difficult to form an effective composite with ZIF-67, resulting in agglomeration and stacking, affecting the adsorption performance. Figure 5 , Figure 6It can be observed that ZIF-67 presents a regular polyhedral crystal structure, and with the increase of the ratio of dimethylimidazole to Co(NO3)2·6H2O, the particle diameter of ZIF-67 gradually decreases from the micrometer scale (2 μm) to the nanometer scale (500 nm). Performance Evaluation

[0057] The adsorbent in the present invention is evaluated for static and dynamic adsorption using formaldehyde as a simulated gas. Place a formaldehyde solution in a sealed desiccator and leave it for 24 hours to allow it to fully volatilize in the desiccator. Weigh 1 g of the adsorbent and place it in a beaker, and weigh its total mass as m1. Place the adsorbent to be tested in a desiccator filled with VOCs gas and leave it for 24 hours. After the time is up, take it out and weigh its mass as m2, calculate its static adsorption capacity, and the test results are shown in Table 1.

[0058] Table 1 Static adsorption capacity

[0059] The following conclusions can be drawn from Table 1: As shown in Table 1, the ZIF-67@ATP adsorption materials prepared in Examples 1, 2, and 3 have a better static adsorption effect on formaldehyde, and the higher the ratio of dimethylimidazole to cobalt nitrate hexahydrate, the better the adsorption capacity, indicating that a smaller particle diameter is more conducive to the adsorption of formaldehyde molecules. The ZIF-67 prepared separately in Comparative Examples 3, 4, and 5 has a poorer adsorption capacity than the ZIF-67@ATP composite material, indicating that the ZIF-67 and attapulgite composite have a synergistic effect in formaldehyde adsorption. At the same time, Comparative Examples 1 and 2 changed the amount of attapulgite added, and the amount of attapulgite added had an effect on the adsorption performance of the composite material. When the ratio of cobalt nitrate hexahydrate to attapulgite reaches 0.656:1, that is, the mass ratio of ZIF-67 to attapulgite reaches 0.08:1, the content of attapulgite is too low, and the performance of the composite material is significantly reduced; when the ratio of cobalt nitrate hexahydrate to attapulgite is less than 0.164:1, that is, the mass ratio of ZIF-67 to attapulgite is less than 0.02:1, excessive attapulgite will cause the stacking and clogging of the composite material. Comparative Example 6 uses ball milling to prepare the adsorption material, and its adsorption capacity is poor, indicating that simply physically mixing ZIF-67 and attapulgite cannot effectively improve the adsorption capacity; and after inserting attapulgite into ZIF-67 to prepare an integrated composite adsorption material, the adsorption performance of the material is significantly improved.

[0060] Dynamic adsorption evaluation was completed in a fixed bed. 1 g of adsorbent (40-60 mesh) was mixed with 4 g of quartz sand (40-60 mesh) and placed in a quartz tube. Quartz wool was used as a pad to prevent the adsorbent from falling. Formaldehyde gas was bubbled out by nitrogen through a bubbling tank at room temperature, and air was introduced as a carrier gas to adjust the gas concentration and air velocity. The concentration of formaldehyde gas was 150 ppm and the air velocity was 10000 h −1 The exhaust concentration is detected in real time by infrared in the in-situ gas pool, and the outlet concentration of 10% of the initial concentration is taken as the penetration concentration, and the corresponding time is the penetration time. The penetration time of gas adsorbed by different adsorbents is compared. The longer the penetration time, the better the adsorption performance. The test results are shown in Table 2-3, and the dynamic penetration curve is shown in Figure 7 and Figure 8 .

[0061] Table 2 Dynamic penetration time of formaldehyde at 0% humidity

[0062] Table 3 Dynamic penetration time of formaldehyde at 80% humidity

[0063] From Tables 2 and 3 Figure 7 , 8 The following conclusions can be drawn: During dynamic adsorption, under a 0% humidity environment, the prepared ZIF-67@ATP composite material has a good formaldehyde adsorption effect. The penetration time of Examples 1, 2, and 3 increases with the increase in the ratio of dimethylimidazole to cobalt nitrate hexahydrate, which are 31 min, 34 min, and 36 min, respectively, which is consistent with the static adsorption trend, indicating that a smaller particle size is conducive to the adsorption of formaldehyde. Comparative Examples 3, 4, and 5 also show the same trend of change, but the penetration time of the pure ZIF-67 material in formaldehyde adsorption is short, and the adsorption effect is poor, indicating that the composite of ZIF-67 and attapulgite can effectively improve the adsorption performance of the material. In Comparative Example 6, the composite material prepared by ball milling has a poor adsorption effect, and the ball milling method cannot well composite ZIF-67 with attapulgite. It can be seen from Comparative Examples 1 and 2 that in the ZIF-67@ATP composite material, the amount of attapulgite added also affects the adsorption performance of the material. Compared with Example 3, it is found that when the ratio of cobalt nitrate hexahydrate to attapulgite is 0.328:1, and the mass ratio of ZIF-67 to attapulgite is 0.04:1, that is, when the amount of attapulgite added is 1 g, the penetration time is the longest.

[0064] In an environment with 80% humidity, the adsorption effect of the adsorption material drops rapidly. Since attapulgite itself has almost no hydrophobic properties, it can be seen from Comparative Example 6 that attapulgite is not effectively compounded with ZIF-67, and the adsorption effect is very poor in a high humidity environment. Similarly, in Comparative Example 2, too much attapulgite is added, and some attapulgite fails to compound with ZIF-67, resulting in poor adsorption effect. Although the penetration time of Examples 1, 2, and 3 has decreased, it still has a longer penetration time than Comparative Examples 2 and 3, reaching up to 14 min. Therefore, when the ratio of dimethylimidazole to cobalt nitrate hexahydrate is 1:10, the ratio of cobalt nitrate hexahydrate to attapulgite is 0.328:1, and the mass ratio of ZIF-67 to attapulgite is 0.04:1, that is, when the amount of attapulgite added is 1 g, the obtained ZIF-67@ATP composite material has the best formaldehyde adsorption effect under 0% humidity and 80% humidity environments.

[0065] The above results show that the ZIF-67@ATP adsorbent prepared by using ethanol as solvent, cobalt nitrate hexahydrate and dimethylimidazole as raw materials, and attapulgite as carrier substrate has a good formaldehyde adsorption effect.

[0066] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A ZIF-67 and attapulgite composite material, characterized in that: The attapulgite is interspersed in the ZIF-67 polyhedral crystal structure to form a sea urchin-like polyhedral crystal structure.

2. The ZIF-67 and attapulgite composite material according to claim 1, characterized in that: The particle size of the ZIF-67 and attapulgite composite material is 200-500nm.

3. The ZIF-67 and attapulgite composite material according to claim 1, characterized in that: The mass ratio of ZIF-67 to attapulgite is 0.02-0.08:

1.

4. The method for preparing the ZIF-67 and attapulgite composite material according to any one of claims 1 to 3, characterized in that: The specific steps include: (1) providing an ethanol solution of cobalt nitrate hexahydrate and an ethanol solution of dimethylimidazole; (2) adding the ethanol solution of dimethylimidazole to the ethanol solution of cobalt nitrate hexahydrate under mechanical stirring conditions, and continuing to stir the reaction to obtain a ZIF-67 precursor solution; (3) Dispersing attapulgite uniformly in a ZIF-67 precursor solution, reacting with stirring at room temperature, allowing to stand for precipitation, collecting the solid product by centrifugation, washing with alcohol, and drying to obtain the ZIF-67 and attapulgite composite material.

5. The method for preparing the ZIF-67 and attapulgite composite material according to claim 4, characterized in that: The mass ratio of dimethylimidazole to cobalt nitrate hexahydrate is 1-10:

1.

6. The method for preparing the ZIF-67 and attapulgite composite material according to claim 4, characterized in that: The mass ratio of cobalt nitrate hexahydrate to attapulgite is 0.15~0.7:

1.

7. The method for preparing the ZIF-67 and attapulgite composite material according to claim 4, characterized in that: In the ethanol solution of cobalt nitrate hexahydrate, the mass concentration of cobalt nitrate hexahydrate is 15-35 mg / mL; in the ethanol solution of dimethylimidazole, the mass concentration of dimethylimidazole is 16-170 mg / mL.

8. The method for preparing the ZIF-67 and attapulgite composite material according to claim 4, characterized in that: The stirring reaction time in step (2) is 1 to 6 hours.

9. The method for preparing the ZIF-67 and attapulgite composite material according to claim 4, characterized in that: The stirring reaction time at room temperature in step (3) is 12 to 24 hours.

10. Use of the ZIF-67 and attapulgite composite material according to any one of claims 1 to 3 in the adsorption of volatile organic compounds.